STUDY OF CHLOROPHYLL-A DISTRIBUTIONS IN LOMBOK STRAIT USING BIOGEOCHEMICAL MODEL BASED ON REGIONAL OCEAN MODELLING SYSTEM (ROMS) - KADEK ARY ANGGRAENI; Takahiro Osawa; I Wayan Arthana (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2012)
Regional Ocean Modelling System (ROMS) has been intended to be a multi-purpose, multi-disciplinary oceanic modeling tool. The Biogeochemical model have coupled to ROMS consists of a system of seven coupled partial differential equations that include: nitrate, ammonium, small and large detritus, phytoplanJ..'ton, zooplankton, and a dynamic phytoplanJ..-ton carbon to chlorophyll ratio. The study of distribution patterns of chlorophyll-a in Lombok Strait (-7 °N - ·10 •sand 114